Preparation And Characterization Of Ph-Sensitive Fish Gelatin Film Containing Anthocyanins Extracted From Rambutan Peel - Hanapi, Hazimah (Universiti Sains Malaysia, 2020)
This study aimed to prepare and characterize a pH sensitive film for intelligent packaging based on fish gelatin doped with anthocyanins extracted from red rambutan peel. The pH sensitive film was prepared by solvent casting method and total anthocyanin content of rambutan peel was determined by pH differential method. The characterization of the film was observed through mechanical, morphological and physical properties of the film. The result from FTIR spectra and SEM of cross section of the films reflects there are intermolecular interactions between fish gelatin and anthocyanins of rambutan peel. The thickness, tensile strength and elongation at break of the films were affected by the concentration of RPE. However, moisture content and water barrier properties of the film were not affected by the concentration of RPE. In addition, the light barrier ability of RPFG film that shown by UV-vis light transmittance is directly proportional with the concentration of incorporated RPE. The color response of the film in the acidic (pH 4) and alkaline (pH 9) showed a low intensity of red color and a low intensity of green respectively. At pH 4 and 9, RPFG3 has the highest ΔE* value compared with RPFG1 and RPFG2 which indicates RPFG3 film has good visual color variability depending on the pH value. Thus, fish gelatin film incorporated with anthocyanins extracted from rambutan peel has a potential to use as a pH indicator of intelligent packaging.